Persistently erected penis in a child for 6 months: A management dilemma - Das Sukanta; Ghosh Dipak; Agarwal Akhilesh; Haldar Suranjan (Wolters Kluwer Medknow Publications, 2008)
Priapism is the presence of a persistent, usually painful, erection of the penis unrelated to sexual stimulation or desire. It is a true emergency requiring urgent intervention. Priapism is frequently idiopathic in etiology, but it is associated with a number of important medical conditions and pharmacologic agents. Cases have been reported in world literature on children having priapism, the etiology of these cases are mostly hematological. Our case is a child having persistently erected penis for more than 6 months. Despite a thorough search, no report of similar case could be found in world literature.